QoS Mechanism With Probability For IPv6-Based IPTV Network. - H.S, Primantara; C.C, Annanda; Budiarto, Rahmat (2009)
A convergence of lP and Television networks, known as IPTV, gains popularity. Unfortunately, today sIPTV has limitation, such as using dedicated private IPv4 network, and mostly not considering "quality ofservice ".